Teaching Strategies with Students’ Learning Interest in English Learning - Nabila Laila; Leni Mardiah Napitupulu; Nabila Irsani; Emeliya Sukma Dara (JURNAL EDUKASI NONFORMAL, 2022)
Teaching strategy is one of the important things and is a way for teachers to support teaching and learning activities in schools. Teaching strategies are also really needed by teachers to increase students' interest in learning during learning activities and make students more interested in learning. In writing this study, the authors analyzed teaching strategies with students' learning interests towards English lessons of MTS Ali Imron Medan students with the aim of knowing what teaching strategies were used by English teachers in English lessons and students' interests in teaching strategies that teachers used in language lessons. England. The type of research used in this study is a qualitative research method. In perfecting the research results, using the interview method with the English teacher at MTS Ali IMron Medan. The results of the study show that students' interest in learning English is determined by the teaching strategies used by the teacher in the classroom. In connection with the results obtained, it is suggested that teachers can use and choose teaching strategies that are liked by students so that students are more interested in learning English.